The Influence of Pesticides on the Biology and Physiology of the Land Snail Bulimulus tenuissimus (Orbigny, 1935) - Patrício, Iza; Martins, Florence Gonçalves; Bonfim, Tatiane Cristina dos Santos; Vasconcellos, Mauricio Carvalho de; Pinheiro, Jairo; Faro, Marta Julia; Mello-Silva, Clélia Christina (International Journal of Environment, Agriculture and Biotechnology, 2019)
Some terrestrial gastropods are agricultural pests and are exposed to toxic products capable of causing physiological and biological alterations. The action of some herbicides and molluscicides has been studied on freshwater snails, but there are few studies of terrestrial species. This study analyzed the biological and physiological responses of Bulimulus tenuissimus exposed to the natural molluscicidal latex of Euphorbia milii var. hislopii and the synthetic herbicide Roundup® Original. A total of 210 snails were divided and exposed for 24 hours to the products (latex or herbicide in concentrations of 1,000 ppm and 100,000 ppm) and type 2 water. Of this total, 150 exposed animals were analyzed biochemically after 24 hours, and the others were observed during 30 days for analysis of the mortality rate. After 24 hours, some snails presented escape mechanisms such as epiphragm formation, cephalopedal mass retraction and burial. The latex did not cause metabolic alterations but the herbicide altered the carbohydrate metabolism of B. tenuissimus, reducing energy substrates in the sites analyzed (hemolymph, digestive gland and cephalopedal mass). Regarding the protein metabolism, there was no alteration after exposure to both analyzed substances. After 30 days of exposure, higher mortality was recorded for the groups exposed to the herbicide. These findings suggest that B. tenuissimus is resistant to the molluscicidal latex of Euphorbia milii var. hislopii more than the herbicide Roundup® Original.